Character Development Through Collaboration Between Teachers, Parents, and Students in Online Learning - I Made Ardana; I. P. Wisna Ariawan; W. Sugandini (Jurnal Edutech Undiksha, 2023)
The teacher still needs to pay more attention to character development. Even though the ultimate goal of learning should be beyond mastering knowledge and skills, there must be character development. The research aimed to obtain a Collaboration Oriented Learning Model product for Teachers, Parents and Students with THK insight (MPbKGOP). This model can make it easier for students to understand mathematical concepts and, at the same time, develop their character. This type of research is research and development (R & D) from Plomp. The research subjects were 70 grade IV students of SDN 1. The THK-oriented MPbKGOP and its devices have been tested through the development stages of the preliminary investigation phase; design phase; realization/ construction phase; test, evaluation, and revision phase, and implementation phase. The data analysis technique used is descriptive qualitative analysis. The study results show that the MPbKGOP with THK insight and its tools are valid, practical and effective. MPbKGOP, along with effective tools, are used to facilitate the understanding of mathematical concepts and character development of students so that there is a shift in character categories that tend to lead to the categories "Developing (B)" and "Cultivating (M)".